Miscibility Development Computation in Enhanced Oil Recovery by Flare Gas Flooding - Tjokorde Walmiki Samadhi; Utjok W.R. Siagian; Angga P. Budiono (Journal of Engineering and Technological Sciences, 2012)
The use of flare gas as injection gas in miscible gas flooding enhanced oil  recovery  (MGF-EOR)  presents  a  potential  synergy  between  oil  production improvement  and  greenhouse  gases  emission  mitigation.  This  work  is  a preliminary evaluation of the feasibility of miscible flare gas injection based on phase behavior computations of  a model oil (43% n-C5H12 : 57% n-C16H34) and a model flare gas (91% CH4  : 9% C2H6). The computations employed the multiple mixing-cell  model  with  Peng-Robinson  and  PC-SAFT  equations  of  state,  and compared the minimum miscibility pressure (MMP) value in the cases of flare gas  injection  and  CO2  injection.  For  CO2  injection,  both  equations  of  state produced  MMP  values  close  to  the  measured  value  of  10.55  MPa.  Flare  gas injection MMP values were predicted to be 3.6-4.5 times those of CO2  injection. This very high MMP implies high gas compression costs, and may compromise the  integrity  of  the  reservoir.  Subsequent  studies  shall  explore  the  gas -oil miscibility  behavior  of  mixtures  of  flare  gas  with  intermediate  hydrocarbon gases and  CO2,  in  order to  identify  a suitable approach for rendering flare  gas feasible as an injection gas in MGF-EOR.